979 views
1 vote
|3 - 10| - (12/4 +2)^2

User Mcmcc
by
6.2k points

2 Answers

3 votes

Answer:

-18

Explanation:

Simplify the following:

abs(3 - 10) - (12/4 + 2)^2

The gcd of 12 and 4 is 4, so 12/4 = (4×3)/(4×1) = 4/4×3 = 3:

abs(3 - 10) - (3 + 2)^2

3 + 2 = 5:

abs(3 - 10) - 5^2

3 - 10 = -7:

abs(-7) - 5^2

5^2 = 25:

abs(-7) - 25

Since -7<=0, then abs(-7) = 7:

7 - 25

7 - 25 = -18:

Answer: -18

User Emyr
by
5.9k points
3 votes

For this case we must resolve the expression:


| 3-10 | - (\frac {12} {4}+2) ^ 2

We have the following definitions:

Different signs are subtracted and the sign of the major is placed.

Absolute value definition:
| -a | = a

Resolving we have:


| 3-10 | = | -7 | = 7


(\frac {12} {4}+2) ^ 2 = (3+2) ^ 2 = 5 ^ 2 = 25

Then, rewriting the expression:


7-25 = -18

Answer:

-18

User Twinkles
by
5.8k points